Estudio de factibilidad para la creación de una empresa dedicada a la producción de harina de banano orgánico en el cantón Quevedo, año 2014 - Rivadeneira Villavicencio, Roberto (2015)
Current research is aimed at developing a feasibility study for the creation of a company dedicated to the production of organic banana flour in the canton Quevedo ,provincia de Los Ríos, and analyzed from the contextualization of the problem through a study of the current situation of the problem, objectives arise, assumptions are made and proper justification; then it is structured and develops the theoretical framework through theoretical, conceptual and legal basis, detailing the most relevant variables according to their objectives and that allowed the development of research; then details the methodology applied, starting from the identification of methods, types, techniques, sources of information, identification of population and the respective sample. Finally the results are presented, for which a market study confirmed that there is an unmet need for flour consumption of organic bananas was performed in the canton Quevedo; technical survey, whereby the production process to be followed by the company to develop the product by the use of raw materials, machinery, equipment, labor, until the final product is determined; economic study allowed us to demonstrate the feasibility of investment through the income statement, on the firth year it is $22.616.93which reflects surplus during the years of the project; financial assessment reflects positive economic indicators by applying the VAN POSSITIVE $462.810.96 and TIR162%. What gives the confidence to invest in this project; it concludes with the presentation d conclusions and recommendations.